Antioxidant Profile of Selenium Enriched Wheatgrass Cultivated under Different Environmental Conditions - Sharma, Shruti (My University, 2012)
The present study was carried out to determine the effected of various environmental conditions such as cultivation in dark, sunlight and under UV light on the selenium induced variations in anti-oxidant profile of wheat grass. Various assays like DPPH, TBARS, total phenolic content and total protein content were used to monitor the antioxidant profile of the wheatgrass. The results indicated that the wheatgrass with high and moderate selenium exhibited potential antioxidant properties as compared to control.
Keywords: Selenium; Wheatgrass; Anti-Oxidant